1991
DOI: 10.1111/j.1528-1157.1991.tb04700.x
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory Effect of Cyclic Alternating Pattern in Focal Lesional and Benign Rolandic Interictal Spikes During Sleep

Abstract: Twenty epileptic patients (10 male and 10 female) were polygraphically recorded during nocturnal sleep. Ten subjects, with a wide age range, were affected by focal lesional epilepsy, and 10 were children affected by benign epilepsy with rolandic spikes (BERS). In five cases a bihemispheric expression of the focal lesional bursts emerged occasionally during the night recordings. The behavior of interictal electroencephalographic (EEG) paroxysms were analyzed with respect to the two arousal states of non-rapid-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
3
4

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 33 publications
1
28
3
4
Order By: Relevance
“…Terzano et al (14,15) developed a microstructural analysis of sleep [phase A and B of the cyclic alternating pattern (CAP)] which they then applied to the study of epileptic phenomena. In particular, focal lesional EEG paroxysms in temporal and frontotemporal epilepsies show a certain activation during phase A of CAP, whereas discharges of idiopathic generalized epilepsies are strongly acti-vated during phase A, and benign rolandic interictal spikes show no significant differences throughout CAP and nonCAP (16)(17)(18).…”
Section: Discussionmentioning
confidence: 95%
“…Terzano et al (14,15) developed a microstructural analysis of sleep [phase A and B of the cyclic alternating pattern (CAP)] which they then applied to the study of epileptic phenomena. In particular, focal lesional EEG paroxysms in temporal and frontotemporal epilepsies show a certain activation during phase A of CAP, whereas discharges of idiopathic generalized epilepsies are strongly acti-vated during phase A, and benign rolandic interictal spikes show no significant differences throughout CAP and nonCAP (16)(17)(18).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies also demonstrated that the frequency and spatial field of interictal spike activity were greater during sleep with spindles compared to wakefulness in children with various forms of epilepsies including focal epilepsy, Landau-Kleffner syndrome and continuous spike-waves during slow wave sleep (Nobili et al, 1999;2001;Luat et al, 2005). Previous studies describing the cyclic alternating pattern of sleep indicated that the phase A with K-complex and slow-waves may be an excitatory phase associated with increased frequency of interictal epileptiform discharges while phase B with low-voltage fast waves, including sleep spindles alone, may be an inhibitory phase (Terzano et al, 1991;Terzano et al, 1992;Zucconi et al, 2000;Eisensehr et al, 2001). A study of adults with temporal lobe epilepsy showed that the firing rate of single neurons in the hippocampus was increased during non-REM sleep compared to wakefulness (Staba et al, 2002).…”
Section: Sleep May Alter the Overall Frequency But Not The Spatial DImentioning
confidence: 99%
“…Traditionally, induction of sleep state by sleep-deprivation has been routinely used to activate interictal spike activity on scalp EEG or magnetoencephalography in patients being evaluated for epilepsy surgery (Kellaway, 1950;Crespel et al, 1998;Xiao et al, 2006). Previous studies have shown that some types of seizures preferentially occur during sleep with spindles, and association between sleep and activation of epileptiform activity on EEG has been of interest to investigators for years (Caveness et al, 1950;Terzano et al, 1991;Nobili et al, 1999;Zucconi et al, 2000;Herman et al, 2001;Steriade and Amzica, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…CAP is indeed a natural arousal rhythm reflecting unstable vigilance, a favorable condition for triggering different types of motor activity, from physiological body movements (16) to nocturnal myoclonus (19), parasomnias (3,18,40) and epileptic manifestations (21,25,(41)(42)(43)(44)(45)(46)(47). Arranged in recurring windows of permission (phase (18) 258 (35) 59 ( 9) 88 (29) 20 ( 6) 95 (39) 21 ( 7) 204 (43) 406 (5 1) 27 ( 5) 11 ( 3) 16 ( 4) 52 ( 4 Tables 1 and 2.…”
Section: Iu-mentioning
confidence: 99%